Molecular docking and molecular dynamic study of multiple medicinal plants’ bioactive compounds as human papillomavirus type 16 E5 protein inhibitor: DOI: 10.48129/kjs.16169 - Arief Hidayatullah; Putra, Wira Eka; Muhaimin Rifa’i; Sustiprijatno; Muhammad Fikri Heikal; Diana Widiastuti; Galuh Wening Permatasari; Hendra Susanto; Adawiyah Suriza Shuib (Kuwait Journal of Science, 2022)
Cervical cancer is the second most prevalent form of cancer in Indonesia. HPV16 and HPV 18 are the leading causes of cervical cancer, accounting for 70-90% of cases. The E5 protein may play a critical role in the disease’s development. Although the HR version of this protein may have some benefits in terms of evading the immune system through MHC I and influencing the cell cycle via p21/p27, very few research have been performed owing to its tiny size and high hydrophobicity. The purpose of this research is to predict the antiviral activity of asarinin and thiazolo[3,2-a]benzimidazole-3(2H)-one,2-(2-fluorobenzylideno)-7,8-dimethyl using molecular docking and molecular dynamics. The docking results showed that the two candidate drugs had a lower docking affinity than rimantadine but comparable stability. Both potent compounds are predicted to disrupt MHC I localization in the ER, the ability of infected cells to proliferate, and the virion assembly process, whereas rimantadine is predicted to disrupt infected cells’ proliferation ability via EGFR regulation and inhibit the activation process of mitogenic signaling in keratinocytes.